Transformasi Pengelolaan Data Penerima Bantuan Sosial melalui Sistem Komputerisasi - Wali, Muhammad; Akbar, Rizaldi; Imilda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
: Managing social assistance recipient data is a critical element in ensuring targeted and accurate aid distribution. This study aims to develop and design a computer-based information system to enhance efficiency, accuracy, and transparency in managing social assistance recipient data in Meureudu Subdistrict. The system was developed using the waterfall approach and software tools such as Microsoft Access 2007 and Microsoft Visual Basic 6.0. The development process involved needs analysis, system design, implementation, and testing. The resulting system includes features such as login, main menu, user and recipient data input forms, data search, and structured report output. The application of normalization methods in the database ensures data is stored accurately and free from duplication. The system is also equipped with criteria-based data search features, enabling users to easily retrieve recipient information. With an intuitive and professional user interface design, this system supports improved decision-making and ensures transparency in aid distribution. The findings indicate that the system has the potential to serve as a model for social assistance management in other regions.